PENINGKATAN KEMAMPUAN PENDIDIK PENDIDIKAN NONFORMAL DALAM IMPLEMENTASI PEMBELAJARAN - Nursam Nursam (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
The role of educator in non-formal education is essential to succeed the non-formal education programs. This article discusses some theoretical knowledge about learning and teaching to improve the educator’s competence. The writer believes that the educators in non-formal education will be able to improve their performance by implementing the theories discussed in this article.